The Green Tide of Macroalgae in The Water of Arabian Gulf, Saudi Arabia; Removal The Nitrogen Compounds By Ulva Intestinalis - El Gammal, Mostafa Abdel Mohsen (International Journal of Scientific Research in Biological Sciences, 2020)
The green tide of macroalgae was recognized as (Ulva fasciata, U. intestinalis, U.flexusa, U. lactuca, U. Chaetomorphalinum, and Enteromorpha intestinalis ) had been regarded in the wintry weather and spring of years, 2016, 2017, and 2018 within the water of Arabian Gulf, Eastern Province, Kingdom of Saudi Arabia. The objective of this study; consider the parameters impact at the blooms of macroalgal and the way can be used this macroalgal to removal the nitrogen compounds like ammonia, nitrite, and nitrate from water aquaculture. Through this period monitor analyses carried out in the coastal water Gulf and the density of macroalgae growth. Indoor carry-out experiments to grow the macroalgae at distinct salinity 5, 10, 15, 20, 25, 30, 35, 40g/l, and remove ammonia, nitrite, and nitrate. The results concluded that the excess of nitrogen compounds and the changed of temperature and salinity were the impact of the principal parameters on green tides seem; the macroalgae (U. intestinalis) may be used to remove ammonia, nitrite, and nitrate from water and the removal percentage decrease with increase and decrease the salinity, the best nitrate compounds removal was at range (10-30 g/l) salinity.